Distinct roles In Vivo for the ubiquitin-proteasome system and the autophagy-lysosomal pathway in the degradation of α-synuclein - Ebrahimi-Fakhari, Darius; Cantuti-Castelvetri, Ippolita; Fan, Zhanyun; Rockenstein, Edward; Masliah, Eliezer; Hyman, Bradley T.; McLean, Pamela J.; Unni, Vivek K. (The journal of neuroscience, 2011)
Increased intracellular levels of α-synuclein are implicated in Parkinson's disease and related disorders and may be caused by alterations in the ubiquitin-proteasome system (UPS) or the autophagy-lysosomal pathway (ALP). A critical question remains how α-synuclein is degraded by neurons in vivo. To address this, our study uses α-synuclein transgenic mice, expressing human α-synuclein or α-synuclein-eGFP under the (h)PDGF-β promoter, in combination with in vivo pharmacologic and multiphoton imaging strategies to systematically test degradation pathways in the living mouse brain. We demonstrate that the UPS is the main degradation pathway for α-synuclein under normal conditions in vivo while with increased α-synuclein burden the ALP is recruited. Moreover, we report alterations of the UPS in α-synuclein transgenic mice and age dependence to the role of the UPS in α-synuclein degradation. In addition, we provide evidence that the UPS and ALP might be functionally connected such that impairment of one can upregulate the other. These results provide a novel link between the UPS, the ALP, and α-synuclein pathology and may have important implications for future therapeutics targeting degradation pathways.